Feasibility of Using Electrocochleography for Objective Estimation of Electro-Acoustic Interactions in Cochlear Implant Recipients with Residual Hearing - Koka, Kanthaiah; Litvak, Leonid M. (Frontiers in Neuroscience, 2017)
Although cochlear implants (CI) traditionally have been used to treat individuals with bilateral profound sensorineural hearing loss, a recent trend is to implant individuals with residual low-frequency hearing. Patients who retain some residual acoustic hearing after surgery often can benefit from electro-acoustic stimulation (EAS) technologies, which combine conventional acoustic amplification with electrical stimulation. However, interactions between acoustic and electrical stimulation may affect outcomes adversely and are time-consuming and difficult to assess behaviorally. This study demonstrated the feasibility of using the Advanced Bionics HiRes90K Advantage implant electronics and HiFocus Mid Scala/1j electrode to measure electrocochleography (ECochG) responses in the presence of electrical stimulation to provide an objective estimate of peripheral physiologic EAS interactions. In general, electrical stimulation reduced ECochG response amplitudes to acoustic stimulation. The degree of peripheral EAS interaction varied as a function of acoustic pure tone frequency and the intra-cochlear location of the electrically stimulated electrode. Further development of this technique may serve to guide and optimize clinical EAS system fittings in the future.